Metal levels in feathers of 12 species of seabirds from Midway Atoll in the northern Pacific Ocean - Burger, Joanna; Gochfeld, Michael (The Science of the total environment, 2000)
Seabirds are excellent subjects for examination of heavy metals because they are long-lived, feed at different distances from land, and exhibit different trophic levels. In this paper we compare the levels of lead, cadmium, mercury arsenic, chromium, manganese, selenium, and tin in the feathers of birds nesting on Midway Atoll in the northern Pacific Ocean. We test the null hypothesis that there are no interspecific differences in the levels of metals in the feathers of the adult black-footed albatross ( Diomedea nigripes), Laysan albatross ( Diomedea immutabilis), red-footed booby ( Sula sula), great frigatebird ( Fregata minor), Bonin petrel ( Pterodroma hypoleuca), Christmas shearwater ( Puffinus nativitatis), red-tailed tropicbird ( Phaethon rubricauda), wedge-tailed shearwater ( Puffinus pacificus), brown noddy ( Anous stolidus), sooty tern ( Sterna fuscata), grey-backed tern ( Sterna lunata), and white tern ( Gygis alba), and young of some of these species. There were interspecific differences in the levels of all metals for adults. Christmas shearwater had the highest levels of lead, cadmium, selenium and manganese, but the second lowest levels of mercury. In general, metal levels were the lowest in the smallest species (white tern), but were not the highest in the largest species (black-footed albatross), except for manganese, arsenic and mercury. There was a high variance in metal levels among adults for some species, but not for others. White tern adults were variable for lead, while Christmas shearwaters were variable for lead and cadmium. Compared to the means for metals in other birds generally (after Burger, 1993), Christmas shearwaters had higher levels of lead, white terns, brown noddy, Christmas shearwater, frigatebirds and Laysan albatrosses had higher levels of cadmium, and bonin petrel, wedge-tailed shearwater, tropicbirds, frigatebirds, red-footed boobies, and both albatrosses had higher levels of mercury. Whereas the means for lead and cadmium were below the known effects levels, some individuals had levels high enough to cause adverse effects in the birds. The mean values for mercury in Bonin petrel, red-tailed tropicbird, and black-footed albatross were higher than the levels known to cause adverse reproductive and behavioral effects.